SWOT Analysis of Potential and Obstacles to Development of Sharia Pawnshops (Study of Sharia Pawnshops Setia Budi Medan Branch) - Fauzi Ahmad Romadhon; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
This study aims to identify and explain all kinds of strengths and weaknesses, as well as opportunities and threats from the Sharia Pawnshop office in Medan. Use SWOT analysis (strengths, Weaknesses, Opportunities, Threats) to minimize existing weaknesses, overcome incoming threats to increase strengths, and use existing opportunities to dominate the market compartment and what strategies are taken to gather all its clients.